Design and development of mechatronic systems at UMinho: a review of some case studies - Silva, Luís F. (2017)
Mechatronics is an interdisciplinary area of engineering that combines mechanical engineering, electrical engineering and information technology. The development methodology for mechatronic systems supports the creation of innovative solutions, improving the reliability and ability of products and reducing their costs. This study reviews some projects (as case studies) that were undertaken by the authors in the area of mechatronics applied to the mechanical, textile, biotechnology and biomedical fields.